A laboratory-friendly protocol for freeze-drying sample preparation in ToF-SIMS single-cell imaging - Shi, Xiujuan; Liu, Mingru; Qi, Yue; Ma, Hongzhe; Wang, Zhaoying; Chen, Yanhua; Abliz, Zeper (Frontiers in Chemistry, 2025)
ToF-SIMS is a high spatial resolution imaging technique for cellular or subcellular analysis of biological samples. Accurate molecular data in single-cell studies depend on proper cell morphology and chemical integrity, highlighting the importance of sample preparation. In this work, we standardized a more efficient freeze-drying method using standard lab materials and improved the sample preparation process. Our comprehensive freeze-drying protocol for cellular samples, encompassing washing, fixation, and drying steps, facilitates the acquisition of enhanced cellular information and ensures high reproducibility. These improvements are poised to significantly advance single-cell mass spectrometry imaging research.